Cell and Organ Printing - Ringeisen, Bradley R.; Spargo, Barry J.; Wu, Peter K.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2010)
Cell and organ printing has become a hot topic of scientific pursuit. Since several early publications between 2000-2003 that demonstrated proof-of-concept, cell and organ printing has blossomed into a rich area for scientific exploration that is being performed by researchers across the globe. Research has thoroughly demonstrated that living cells can be printed via a number of actuations including electrospray, extrusion via micropens and ejection through photothermal, thermal or optical mechanisms. This topic has come of age and it is ripe for exploring the underpinnings of the research to date. We have included research that uses printing technology to deposit or guide cells for tissue engineering applications and for completeness, we have also included chapters describing bacteria printing, biomolecular printing that could be used to build growth factors or recruitment macromolecules into scaffolds, tissue microdissection, as well as live cell printing. The breadth of approaches includes 3D freeform fabrication, ink jet, laser guidance and modified laser direct write techniques. We hope that this book is not the final word but the first word, defining how these tools have been used to take the first steps towards the ultimate goal of creating heterogeneous tissue constructs. Only time will tell whether cell printers will truly become organ printers, but the technologies described in this book hold promise to achieve what the field of regenerative medicine requires - functional 3D scaffolds with multiple cell types differentiated into functional tissue!
Biological Freeform Fabrication -- 3D On-Demand Bioprinting for the Creation of Engineered Tissues -- Ink Jet Approaches -- Reconstruction of Biological Three-Dimensional Tissues: Bioprinting and Biofabrication Using Inkjet Technology -- Piezoelectric Inkjet Printing of Cells and Biomaterials -- Modified Laser Induced Forward Transfer (LIFT) Approaches -- Laser-Induced Forward Transfer: A Laser-Based Technique for Biomolecules Printing -- Biological Laser Printing (BioLP) for High Resolution Cell Deposition -- High-Throughput Biological Laser Printing: Droplet Ejection Mechanism, Integration of a Dedicated Workstation, and Bioprinting of Cells and Biomaterials -- Absorbing-Film Assisted Laser Induced Forward Transfer of Sensitive Biological Subjects -- Laser Guidance Approaches -- Laser Guidance-Based Cell Micropatterning -- Self Organization and Biological Guidance -- What Should We Print? Emerging Principles to Rationally Design Tissues Prone to Self-Organization -- Biological Guidance -- Patterning Cells on Complex Curved Surface by Precision Spraying of Polymers -- Fabrication of Growth Factor Array Using an Inkjet Printer -- 3-Dimensional Scaffold Cell Printing -- 3D-Fiber Deposition for Tissue Engineering and Organ Printing Applications -- Printing Bacteria -- Bacterial Cell Printing.
Keywords: Medicine; Biomedicine; Biomedicine general